ANALISIS PROMOSI MAKANAN KHAS MELAYU BOLU KEMOJO PADA GERAI AL MAHDI PEKANBARU - Sari, Indah Puspita; Achnes, Syofia; Agus, Ari Kresnaputra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The aim of this research is to find out the respondents’ responses from an analysis on promoting Malay cuisine kemojospongecake which being sold by Al Mahdi food stall Pekanbaru that using marketing mix (advertising and personal selling).The theory used in this research is Lupioyadi and Hamdany (2006 :74) that separated promotion mix into six parts; advertising, personal selling, sales promotion, public relation, word of mouth, and direct mail.The method of the research is qualitative research which the research and comprehension process based on social phenomenon and public affair investigation. In this research, the writer used Ordinal Scale in measuring the data and Likert’s Scale in measuring person’s attitude upon object’s attitude.This research is identified into two problems; advertising and personal selling that being operated by Al Mahdi food stall Pekanbaru. Thus in this research, the writer this research can reveal the respondents’ response on two promotions mix by distributing questionnaires to respondents and also processing the result of questionnaires.The conclusion of this research, it showed the respondents’ responses on marketing mix on advertising were interesting enough based on the analysis, yet on personal selling also was good based on the analysis which those results based on the questionnaires answers recapitulation. Then, the writer suggested the company in advertising analysis to be more innovative on social media and improve the features on the social media for selling promotion,Key words: Promotion, kemojo sponge cake, and populations’ responses on two marketing mix.